The constructive evolution of taste in Astyanax cavefish: A review - Berning, Daniel; Gross, Joshua B. (Frontiers in Ecology and Evolution, 2023)
Animals inhabiting subterranean environments tend to evolve a constellation of ‘regressive’ and ‘constructive’ features. Regressive traits like vision and pigmentation are reduced or lost in derived organisms. In contrast, constructive traits like non-visual sensation, are commonly augmented and evolving under strong selection. Numerous studies have examined the genetic, developmental and molecular bases for regressive traits, while constructive traits have received less attention. A key constructive sensory feature in cave animals is the gustatory system which is intuitively useful for animals living in complete darkness, given the need to secure food for survival. Interestingly, despite having been studied for decades in the Mexican tetra, Astyanax mexicanus, much remains unknown regarding the biological basis, and adaptive relevance, of taste system evolution in cave morphs. Here, we present a brief review of taste system research in this system, conducted over the past 90 years. We underscore key differences in gustation between cave and surface fish that reside at the levels of anatomy, perception and behavior. From this review, we sought to identify key knowledge gaps in our understanding of constructive taste system evolution. Future studies will provide further insights to the nature of constructive trait evolution by determining if constructive and regressive traits evolve through similar or different genetic and developmental mechanisms, and provide an essential case study for examining convergence of constructive traits across geographically distinct populations.